Wetland as revitalization pond at urban area based on the eco hydrology concept - Adek Rizaldi, M; Montarcih Limantara, Lily (International Journal of Engineering and Technology, 2018)
Universitas Indonesia (UI) has a campus in Depok with six ponds, five of which are artificial ponds and one of the catchment area that operates in the central Ciliwung Sub-watershed. The ponds (Kenanga, Agathis, Mahoni, Puspa, Ulin and Salam "KAMPUS") are designed as one of the catchment area, referring to Presidential Decree No. 32/1990 about the management of protected areas, ponds as catchment areas, flood controllers, and groundwater runoff. However, due to uncontrolled development in the catchment area of the UI pond system, KAMPUS cascade ponds transformed into a "toilet" which accommodates the liquid and solid waste of its catchment area. The mechanism designed for management in the KAMPUS cascade pond system is to utilize the cascade pond as a stabilization pond (improving water quality). One of them is utilizing Agathis cascade pond as a constructed stormwater wetland system, which is a pretreatment for the inflow to the KAMPUS pond system. This constructed wetland design is planned with several mechanisms: precipitation, filtering, chemical process by utilizing plants for absorption, nutrient transformation and eliminating pathogens. The result shows that this constructed wetland gives the water quality improvement percentage up to 87%. Water quality on effluent conforms with the water quality standards for irrigation and planting (grade 4) referring to Government Regulation No. 82/2001 about Water Quality Management and Pollution Control.Â